-6(t-7)-(t+3)=4

Simple and best practice solution for -6(t-7)-(t+3)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(t-7)-(t+3)=4 equation:


Simplifying
-6(t + -7) + -1(t + 3) = 4

Reorder the terms:
-6(-7 + t) + -1(t + 3) = 4
(-7 * -6 + t * -6) + -1(t + 3) = 4
(42 + -6t) + -1(t + 3) = 4

Reorder the terms:
42 + -6t + -1(3 + t) = 4
42 + -6t + (3 * -1 + t * -1) = 4
42 + -6t + (-3 + -1t) = 4

Reorder the terms:
42 + -3 + -6t + -1t = 4

Combine like terms: 42 + -3 = 39
39 + -6t + -1t = 4

Combine like terms: -6t + -1t = -7t
39 + -7t = 4

Solving
39 + -7t = 4

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-39' to each side of the equation.
39 + -39 + -7t = 4 + -39

Combine like terms: 39 + -39 = 0
0 + -7t = 4 + -39
-7t = 4 + -39

Combine like terms: 4 + -39 = -35
-7t = -35

Divide each side by '-7'.
t = 5

Simplifying
t = 5

See similar equations:

| 2(x+1)+5(x-1)=7 | | 7x+9x=80 | | -2(t-6)-(t+9)=1 | | 9x^2-100=0 | | x=0.9x+0.3(1-x) | | 5-8x=135-43x | | 5-2g=-10-0.5g | | 4x+9=-75-8x | | 4m+6=7m+12 | | -18-6*-1=6(1+3*-1) | | 9(m+2)=-(m+7) | | .25+.5t=4 | | 5k+6k+7k=90 | | 6(b+7)=4(2b) | | -.25w-3=w+.333 | | 3x+14=3(x+7) | | -2(a+3)=-4 | | 5(x-6)=45 | | 116-4x=x+8 | | x=6371*cos*51.247*cos*22.559 | | 65-2x=13-8x | | 5-10x=83-31x | | x^2-x=4 | | 2x-3=5x-15 | | 12x+2= | | 2x^2-3x-35=345 | | 84-3x=2x+19 | | y^2-40y+720=0 | | 16x-198=6x-8 | | 2x^2-345=3456 | | 8x+27=2x+99 | | 88-5x=22x+16 |

Equations solver categories